Help your kids with computer coding: a unique step-by-step visual guide, from binary code to building games - Vorderman, Carol (DK Publishing, 2019)
From coding basics to fun projects, this guide will inspire children to use their imagination and problem-solving skills to build games and animations using two different programming languages--Scratch 3.0 and Python.